OSBP is a Major Determinant of Golgi Phosphatidylinositol 4-Phosphate Homeostasis - Colleen P. Doyle; Liz Timple; Gerald R. V. Hammond (Contact, 2024)
The lipid phosphatidylinositol 4-phosphate (PI4P) plays a master regulatory role at Golgi membranes, orchestrating membrane budding, non-vesicular lipid transport and membrane organization. It follows that harmonious Golgi function requires strictly maintained PI4P homeostasis. One of the most abundant PI4P effector proteins is the oxysterol binding protein (OSBP), a lipid transfer protein that exchanges trans-Golgi PI4P for ER cholesterol. Although this protein consumes PI4P as part of its lipid anti-porter function, whether it actively contributes to Golgi PI4P homeostasis has been questioned. Here, we employed a series of acute and chronic genetic manipulations, together with orthogonal targeting of OSBP, to interrogate its control over Golgi PI4P abundance. Modulating OSBP levels at ER:Golgi membrane contact sites produces reciprocal changes in PI4P levels. Additionally, we observe that OSBP has a high capacity for PI4P turnover, even at orthogonal organelle membranes. However, despite also visiting the plasma membrane, endogenous OSBP makes no impact on PI4P levels in this compartment. We conclude that OSBP is a major determinant of Golgi PI4P homeostasis.